Effects of the kinase inhibitor sorafenib on heart, muscle, liver and plasma metabolism in vivo using non‐targeted metabolomics analysis. (24th November 2017) - Jensen, Brian C; Parry, Traci L; Huang, Wei; Beak, Ju Youn; Ilaiwy, Amro; Bain, James R; Newgard, Christopher B; Muehlbauer, Michael J; Patterson, Cam; Johnson, Gary L; Willis, Monte S
Abstract : Background and Purpose: The human kinome consists of roughly 500 kinases, including 150 that have been proposed as therapeutic targets. Protein kinases regulate an array of signalling pathways that control metabolism, cell cycle progression, cell death, differentiation and survival. It is not surprising, then, that new kinase inhibitors developed to treat cancer, including sorafenib, also exhibit cardiotoxicity. We hypothesized that sorafenib cardiotoxicity is related to its deleterious effects on specific cardiac metabolic pathways given the critical roles of protein kinases in cardiac metabolism. Experimental Approach: FVB/N mice (10 per group) were challenged with sorafenib or vehicle control daily for 2 weeks. Echocardiographic assessment of the heart identified systolic dysfunction consistent with cardiotoxicity in sorafenib‐treated mice compared to vehicle‐treated controls. Heart, skeletal muscle, liver and plasma were flash frozen and prepped for non‐targeted GC–MS metabolomics analysis. Key Results: Compared to vehicle‐treated controls, sorafenib‐treated hearts exhibited significant alterations in 11 metabolites, including markedly altered taurine/hypotaurine metabolism (25‐fold enrichment), identified by pathway enrichment analysis. Conclusions and Implications: These studies identified alterations in taurine/hypotaurine metabolism in the hearts and skeletal muscles of mice treated with sorafenib. Interventions that rescue or prevent these sorafenib‐induced changes, such as taurine supplementation, may be helpful in attenuating sorafenib‐induced cardiac injury.